2010
DOI: 10.1002/ange.201002919
|View full text |Cite
|
Sign up to set email alerts
|

Direkter Ylidtransfer auf Carbonylverbindungen und Heteroarene

Abstract: Power‐Transfer: Die Titelreaktion (siehe Schema) verläuft unter milden Bedingungen (Raumtemperatur, kurze Reaktionszeit) und liefert ausgehend von methylenaktiven und heteroaromatischen Verbindungen Sulfonium‐Ylide in einem einzigen Schritt und in sehr hohen Ausbeuten. Ein detaillierter Strukturvergleich einer Vielzahl von Yliden wird genutzt, um den Einfluss der Struktur auf die Reaktivität dieser Verbindungen zu diskutieren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…We then examined the scope of this simple yet highly effective procedure for the intramolecular preparation of bicyclic furans. Importantly, all the alkynyl sulfonium ylides employed as substrates could be readily accessed by direct ylide transfer in very high yields according to our previously reported procedure 8. Their stability towards chromatography and recrystallization along with their crystallinity renders them easily handled substrates for subsequent transformations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then examined the scope of this simple yet highly effective procedure for the intramolecular preparation of bicyclic furans. Importantly, all the alkynyl sulfonium ylides employed as substrates could be readily accessed by direct ylide transfer in very high yields according to our previously reported procedure 8. Their stability towards chromatography and recrystallization along with their crystallinity renders them easily handled substrates for subsequent transformations.…”
Section: Methodsmentioning
confidence: 99%
“…Initial studies focused on the alkynyl sulfonium ylide 1 a , readily available by direct ylide transfer8 to the corresponding ketoester. Exposure of this compound to diverse gold(I) promoters led to sharply contrasting results (see the Supporting Information for details), and it was found that the simple combination of commercially available PPh 3 AuCl and AgSbF 6 led to quantitative conversion into the furofuranone 2 a at room temperature within 3 h 9…”
Section: Methodsmentioning
confidence: 99%
“…The decomposition of diazo compounds in the presence of HBF 4 and sulfides generates sulfonium salts, which, after addition of base, lead to sulfonium ylides 36. Two interesting and direct methods for the synthesis of sulfonium ylides were described by Cook and Moffatt,37a and recently by Maulide and co‐workers 37b,37c. Maulide and co‐workers employed Martin's sulfurane for direct ylide transfer to ketones, diketones, and keto esters in very good yields and under mild conditions (Scheme ).…”
Section: Preparation Of Sulfur Ylidesmentioning
confidence: 99%
“…We recently developed a new methodology to directly access stabilized sulfonium ylides in a single step, by a process termed ylide transfer. [5] Those compounds display unique reac-tivity and electronic features, lending themselves to interesting applications featuring gold catalysis, [6,7] including an unusual intramolecular olefin cyclopropanation through catalytic olefin activation. [8] Herein, we describe an intermolecular gold-catalyzed synthesis of alkylidenecyclopropanes employing sulfonium ylides and activated allenes, [9] as well as mechanistic studies on this transformation (Scheme 1b).…”
mentioning
confidence: 99%